EVALUASI TINGKAT KEPUASAN PASIEN DIABETES MELITUS TERHADAP PELAYANAN INFORMASI OBAT DI PUSKESMAS KARAWANG - Maya Arfania; Seputri Nonifili Daeli; Yuliana Latifah (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2022)
Drug information service is one part of pharmaceutical services. Providing accurate and complete drug information can support the provision of good health services to the community because it can increase the efficacy and safety of drug use. The purpose of this study was to determine the level of patient satisfaction with drug information services at the Karawang District Health Center. This study is a descriptive study with a cross sectional design, to describe the level of patient satisfaction with DM drug information services at the Karawang Health Center. The number of samples was 176 patients. The results of this study, most of the patients were very satisfied with the drug information services provided by pharmacy officers at the Puskesmas.